PENGARUH MOTIVASI, KOMPENSASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI SEKOLAH BODHI DHARMA - febriyanti, kanti; Heryenzus,S.Kom., Msi (SCIENTIA JOURNAL, 2022)
This review intends to determine how the impact of Motivation, Compensation, and career development on the Performance of Bodhi Dharma School Employees. The researcher took data on 112 employees of the Bodhi Dharma School who were respondents using a saturated sample. Information retrieval technique is used with the help of SPSS. The results of the investigation of information in this review indicate that motivation has a positive effect on employee performance with a t value of 2,208 > t table 1,65895, compensation basically affects the execution of representatives, T count 2,323 > t table 1,65895, compensation has a significant effect on employee performance. with tcount 8.830 > t table 1.65895 and motivation, compensation and career development simultaneously affect performance with F count 35.240 > F table 3.93. The test results of the determinant coefficient obtained 0.492 or 49.5% which implies the commitment of motivation, compensation and career development factors to performance is 49.5%, the rest is influenced by various factors outside this review.